Effectof SrTiO3nano-crystals on the dielectric properties ofNa0.47K0.47Li0.06NbO3ceramics by seed-induced method - Uraiwan Intatha (2018)
© 2016 Trans Tech Publications, Switzerland. A solid-state reaction method is generally used to fabricate ceramics. This work studies the influence of heterogenous nano-crystallites on electrical properties of lead free Na0.47K0.47Li0.06NbO3(NKLN) ceramics by adding SrTiO3nano-crystals as the initial phase of reaction. The lead-free piezoelectric ceramics were synthesized by the seed-induced method. The SrTiO3nano-crystals used as seeds were prepared by molten salt technique. The seed content was varied from 0 to 10.0 mol%. The investigation reports microstructure and electrical properties of ceramics. The XRD showed a mixed tetragonal and orthorhombic phase structure. Tcdecreasing with increased SrTiO3nano-crystal concentration.